2011
DOI: 10.1586/egh.11.23
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: beyond the boundaries of the bowel

Abstract: Dysregulated inflammation in the gut, designated clinically as inflammatory bowel disease (IBD), is manifested by the prototypic phenotypes of an Arthus-like reaction restricted to the mucosa of the colon, as in ulcerative colitis, or a transmural granulomatous reaction, as in Crohn's disease, or an indeterminate form of the two polar types. That the inflammation of IBD can trespass the boundaries of the bowel has long been known, with articular, ophthalmologic, cutaneous, hepatobiliary or other complications/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…NF-κB is increased in the lesions of CD, as are numerous inflammatory cytokines whose transcription is mediated by NF-κB, including tumor necrosis factor alpha (TNF-α), and proinflammatory cytokines like interleukin-1 (IL-1), IL-6, and IL-12 [5][6][7]. Th1 polarization mediated by IL-2 and interferon γ (IFN-γ ) is critical for the initiation and continuation of a specific immune response.…”
Section: Adhesion Molecule Treatment Of Ibd mentioning
confidence: 99%
“…NF-κB is increased in the lesions of CD, as are numerous inflammatory cytokines whose transcription is mediated by NF-κB, including tumor necrosis factor alpha (TNF-α), and proinflammatory cytokines like interleukin-1 (IL-1), IL-6, and IL-12 [5][6][7]. Th1 polarization mediated by IL-2 and interferon γ (IFN-γ ) is critical for the initiation and continuation of a specific immune response.…”
Section: Adhesion Molecule Treatment Of Ibd mentioning
confidence: 99%
“…Another possible mechanism can be donor lymphocytes having the genetic information for an abnormal inflammatory response. Further, in colonic mucosa, failure of physiological control by donor-derived regulatory T cells causes intestinal inflammation, which may demonstrate itself as an Arthus-like reaction (22). In a previous study, the use of anti-TNFα showed dramatic clinical and histological improvement in two children (23).…”
Section: Immunological Complicationsmentioning
confidence: 99%
“…Rather, transitioning from rural to metropolitan life, switch from fresh prevalently vegetarian food to elaborated meat recipes, changes of feeding times due to work shift, may have shocked the microbiome, which did not keep pace with the rapid changes [76]. There is an extremely abundant literature summarizing the wealth of knowledge accumulated in a century of studies on IBD [77,78]; of an utmost interest is the report of recent epidemics-like IBD episodes in countries like Iran, where life and feeding habits have been partially Westernized [79]. A thorough scrutiny of these issues is provided in a recently published paper [80].…”
Section: Clinics Of Inflammation (The Positive Janus Face At the Digementioning
confidence: 99%